Additive predictive power of the CHA2DS2-VASc and HAS-BLED scores for mortality in patients with atrial fibrillation. (25th November 2020) - Morrone, D; Kroep, S; Ricci, F; Renda, G; Patti, G; Kirchhof, P; Chuang, L.C; Van Hout, B; De Caterina, R
Abstract: Background and objectives: In atrial fibrillation (AF), assessment of thromboembolic and bleeding risks are recommended to prescribe anticoagulation for stroke prevention. However, AF also increases mortality, and predictors of death are less characterized than predictors for stroke. We investigated the predictive power for mortality of the CHA2DS2-VASc, the HAS-BLED score and their combination. Methods: Individual patient data were analyzed from the PREvention oF thromboembolic events-European Registry in Atrial Fibrillation (PREFER AF), a prospective real-world registry with a 12-month follow-up, with a total of 7243 patients enrolled from 461 hospitals and 7 European countries (Austria, France, Germany, Italy, Spain, Switzerland, and United Kingdom). Logistic regression was used to analyze the relationship of the CHA2DS2-VASc and HAS-BLED scores, and their combinations with outcome events, including mortality, at one year. The predictive ability of the scores was analyzed by comparing c-statistics. Results: The study sample consisted of 5, 209 AF patients with complete information on both scores. Mean age was 71.8±10.46 years; 3145 subjects (60.4%) were male. Events rate of stroke/SEE and major bleeding at one-year were 2.3% (122 patients) and 2.9% (149 patients), respectively. At one year, 3.1% of patients died (160 out of 5, 209). Both scores had broadly similar c-statistics; for CHA2DS2-VASc: 0.637, 0.656 and 0.616 for models predicting mortality, SSE and major bleeding, respectively; for HAS-BLED: 0.620, 0.647, and 0.627, respectively. When including the individual components of both scores separately, c-statistics increased to 0.715, 0.694 and 0.636 with CHA2DS2-VASc, and to 0.681, 0.697 and 0.680 with HAS-BLED. The predictive power with both scores combined, removing overlapping components, was higher, with a c-statistic of 0.74, 0.73 and 0.70 for mortality (Table), SSE and major bleeding, respectively. Conclusion: Both the CHA2DS2-VASc and the HAS-BLED score predict mortality similarly in AF, and a combination of the score components increases prediction significantly. Such combination may thus be clinically useful. Funding Acknowledgement: Type of funding source: None